Insufficient cerebral venous drainage predicts early edema in acute intracerebral hemorrhage. (8th October 2019) - Chen, Lin; Xu, Mengjun; Yan, Shenqiang; Luo, Zhongyu; Tong, Lusha; Lou, Min
Abstract : Objectives: To explore the relationship between insufficient ipsilateral cerebral venous drainage and the development of perihematomal edema (PHE) and functional outcome in patients with acute intracerebral hemorrhage (ICH). Methods: We retrospectively reviewed our prospectively collected database for patients with acute spontaneous supratentorial ICH and analyzed patients who underwent baseline CT perfusion (CTP) within 6 hours of onset and noncontrast CT at 24 hours. Absence of filling of 1 or more of the ipsilateral superficial middle cerebral vein, vein of Trolard, vein of Labbé, basal vein of Rosenthal, and internal cerebral vein, evaluated on venous maps generated from baseline CTP, was identified as absent ipsilateral venous filling (AIVF). Relative PHE (rPHE) was calculated as the ratio of PHE volume to hematoma volume on follow-up CT. Results: A total of 138 patients were included. Median absolute PHE volume on follow-up CT was 3.5 (1.0–9.3) mL and rPHE was 24.3% (9.0%–49.4%). One absent ipsilateral vein was observed in 38 (27.5%) patients, and 2 absent veins were observed in 5 (3.6%) patients. Multivariate analysis showed that AIVF was independently associated with large rPHE at 24 hours (odds ratio [OR] 4.032, 95% confidence interval [CI] 1.739–9.347, p < 0.001). Large PHE volume was independently associated with poor outcome (OR 1.109, 95% CI 1.009–1.218, p = 0.031). Conclusion: AIVF was observed in about one-third of patients with acute ICH, which might be attributed to hypoperfusion after ICH and was strongly related to the development of PHE. Identification of cerebral venous filling status might be a promising imaging marker for PHE and a potential therapeutic target in ICH.